Commodity Price Shocks and Fiscal Outcomes - Samake, Issouf (IMF Working Papers; Working Paper ;, 2012)
The experience of developing countries over 1990-2010 indicates that commodity prices have a significant impact on fiscal outcomes. Both revenue and expenditure rise in response to commodity (import or export) price increases; the response of the fiscal deficit is ambiguous. A floating exchange rate regime only partially offsets the impact; foreign-exchange reserves do not dampen the effects. Hence, there is a strong case for fiscal hedging against commodity price shocks. Hedging instruments based on a limited set of benchmark world prices for a narrow set of commodities may suffice to realize most of the potential benefits.